Karrikins: A new family of plant growth regulators in smoke - Chiwocha, S.; Dixon, Kingsley; Flematti, G.; Ghisalberti, E.; Merritt, D.; Nelson, D.; Riseborough, J.; Smith, S.; Stevens, J. (Elsevier Science, 2009)
Karrikins are a chemically defined family of plant growth regulators discovered in smoke from burning plant material. Karrikins are potent in breaking dormancy of seeds of many species adapted to environments that regularly experience fire and smoke. The recent discovery that karrikins trigger seed germination and control seedling growth in taxa that would rarely experience fire indicates that their significance could extend far beyond fire ecology. This is exemplified by new studies showing that seeds of Arabidopsis thaliana respond sensitively and specifically to karrikins in smoke. These exciting discoveries might be explained if karrikins are produced in the environment by processes other than fire, such as by chemical or microbial degradation of vegetation in response to disturbance of the soil or removal of the plant canopy. Another hypothesis is that plants contain endogenous karrikins that function naturally in the control of seed germination and that species from fire-prone habitats have evolved to respond also to exogenous karrikins. A variant on this hypothesis is that karrikins mimic endogenous plant hormones such as terpenoids that control seed germination. The evidence for these hypotheses is discussed, but whatever the explanation karrikins are now firmly established as an important family of naturally occurring plant growth regulators. © 2009 Elsevier Ireland Ltd. All rights reserved.